Salpingea pathology in the tubal ectopic pregnancy - Vega Rizo Patrón, Leoncio (2015)
96 cases diagnosed as "ectopic pregnancies salpíngeos", belonging to the archives of the Institute of Pathology, Faculty of Medicine UNMSM, in the Loayza Hospital. Were studied histologically, retrospectively Sixty of these cases had used medical records. In the group of the most common injuries was pure follicular chronic Salpingitis with 22 cases (22.9%) followed in order of frequency simple chronic salpingitis with 18 cases (18.8%) and finally the isthmic salpingitis nodosa with 16 cases (16.6% ). Among the classified as "mixed" the highest percentage corresponded to cases in which concomitant lesions such nodosa follicular isthmus and chronic Salpingitis Salpingitis was 6 cases (6.3%), following cases of isthmic nodosa Chronic Salpingitis Salpingitis and simple: 3 cases (3.1%). This work shows the importance of the inflammatory lesions salpíngeas in the genesis of tubal ectopic pregnancy and the important but little known role of salpingitis isthmic nodosa in this process.